THE INFLUENCE OF VOLCANO ERUPTION EXPERIMENTS ON THE COGNITIVE DEVELOPMENT OF CHILDREN IN GROUP B1 IN TK AL- HIKMAH - Rosida; Ruqoyyah Fitri (International Journal of Teaching and Learning, 2024)
This study aims to examine the impact of a volcanic eruption experiment on the cognitive development of early childhood students at TK Al-Hikmah Ketapang Banyuwangi. Using an experimental method with a One-Group Pretest-Posttest design, the sample consisted of 15 children from group B1. The results showed a significant increase in the children's cognitive abilities after the treatment. Before the treatment, most children were in the "Not Yet Developed" and "Starting to Develop" categories. After the treatment, there was a significant increase to the "Developing as Expected" and "Developing Very Well" categories. The Wilcoxon test indicated that this experiment positively influenced the children's cognitive development. Nature-based science learning not only enhances cognitive abilities but also motivation, social skills, and both physical and mental health of children. This method is effective in integrating direct experiences with the natural environment to prepare children for future challenges.